(untitled) (Acta Entomologica Serbica, 2023)
Heteropteran fauna of Serbia has increased by six newly recorded species: Macrolophus costalis Fieber, 1858, Macrolophus rubi Woodroffe, 1957, Charagochilus spiralifer Kerzhner 1988, Maurodactylus albidus Kolenati, 1845, Phoenicocoris dissimilis (Reuter, 1878), and Plesiodema pinetella (Zetterstedt, 1828). All of them belong to the family Miridae.